1989
DOI: 10.1115/1.3265694
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Tube-to-Support Dynamic Interaction in Heat Exchange Equipment

Abstract: Tubes within tube and shell heat exchange components are supported at intermediate points by support plates. Flow-induced vibration of a tube can cause it to impact or rub against a support plate or against adjacent tubes and can result in tube fretting-wear. The tube-to-support dynamic interaction is used to relate experimental wear data from test rigs to real multi-span heat exchanger configurations. Analytical techniques are required to estimate this interaction in real heat exchangers. Simulation results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The random fluid forces were transformed by the power spectral density (PSD) in references. 27,28 The representation of the turbulence forces utilized in this research is shown in Eq. (7).…”
Section: Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The random fluid forces were transformed by the power spectral density (PSD) in references. 27,28 The representation of the turbulence forces utilized in this research is shown in Eq. (7).…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Several contact models are proposed such as the force balanced friction model (FBFM), velocity limited friction model (VLFM) and spring damper friction model (SDFM) to investigate the vibration of loosely supported tubes. 18,19 Robert J. Rogers carried out simulation study based on VLFM model. 20,21 J. Antunes 22 studied loosely supported tubes under fluid-elastic instability and turbulence excitation through SDFM model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root mean square (RMS) values of contact force were found to have an effect on the fretting wear. Fisher and Chow (1995) and Fisher et al (1989) performed fretting wear measurements on different material combinations and support-plate geometries. Through these research studies, the normal work rate model was proposed, in which the volume wear rate can be described as:…”
Section: Introductionmentioning
confidence: 99%
“…Initiation, stability, and growth characteristics of the damage caused by this mechanism are a function of a large number of variables including the support locations, the stiffness of the supports, the gap size between tube and support, secondary flow velocities and directions, and oxide layer characteristics. Fretting wear degradation was first identified as a concern in the early 1970s and has been noted to some degree in all major PWR steam generator designs in the world, and consequently Electric Power Research Institute, Atomic Energy of Canada Limited, and Korea Electric Power Research Institute etc., have sponsored some projects to investigate the fretting wear behavior of steam generators tube [3][4][5][6][7][8][9][10][11][12][13][14][15], however, no investigations have been carried out in China. So, it is emergent and necessary to study the fretting wear behavior of steam generators tube for the structural integrity evaluation and life prediction of steam generators in China.…”
Section: Introductionmentioning
confidence: 99%